2000
DOI: 10.1108/13522750010349305
|View full text |Cite
|
Sign up to set email alerts
|

Do services exporters build relationships? Some qualitative perspectives

Abstract: Investigates whether success factors for Australian services firms that export to Asia are consistent with the theory of relationship marketing, and demonstrates the power of the in‐depth interview methodology for exploring marketing theory. Relationship marketing theory suggests that services firms should adopt a relationship marketing approach while goods firms might use a transactional approach. To investigate this theory, a series of in‐depth interviews were conducted in firms marketing agribusiness produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 13 publications
0
24
1
Order By: Relevance
“…Therefore, a qualitative approach was adopted due to it ability to obtain a fi rst-hand description of a specifi ed domain of experience. 38,39 In this sense, understanding is derived from information gained directly from the employee, rather than from the direction of theories, laws and concepts. 40 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a qualitative approach was adopted due to it ability to obtain a fi rst-hand description of a specifi ed domain of experience. 38,39 In this sense, understanding is derived from information gained directly from the employee, rather than from the direction of theories, laws and concepts. 40 …”
Section: Methodsmentioning
confidence: 99%
“…The research questions along with the corresponding umbrella questions are shown in Table 1 . Following a line of thought similar to that of Hastings and Perry, 39 a convergent interviewing technique was used, whereby the interviews continued until there was zero sum gain from conducting anymore.…”
Section: Data Collectionmentioning
confidence: 99%
“…Convergent interviewing is a cyclical data collection, analysis and interpretative technique that uses a limited number of interviews with participants who possess knowledge and experience in the area of interest ( Dick, 1990 ). This process encourages a ' series of successive approximations ' ( Dick, 1990, p. 3 ) leading to a consensus through the development and use of probe questions about important information where interviewee agreement or disagreement is tested ( Hastings and Perry, 2000 ). Using this approach, interviewer preconceptions are (ideally) removed from the information-gathering process by allowing respondents to self-identify salient points that can be tested in subsequent interviews.…”
Section: Methodsmentioning
confidence: 99%
“…When firms want to build up personal relationships, carry out on-site research, and understand the needs of the host country buyers and markets then high control modes are preferred (Hastings & Perry, 2000). Zahra et al in (2000) indicated that high control foreign market entry modes still remain much more conducive environment for fast technology learning firms.…”
Section: Market Entry Modesmentioning
confidence: 99%